Pengaruh Komite Audit dan Firm Size terhadap Financial Restatement: Tinjauan Perspektif Pengujian Substantif pada Perusahaan BEI 2021–2023 - Nasrullah Asri; ST Ainun Khairunnisa; Nawrah Qanita Irfan; Mar’ah Aulia; Silviah Bahrun; Falisha Sulistiawati; Alia Rezki Amalia (AKUNTANSI 45, 2025)
Accurate financial statements play a vital role in supporting investor decision making, yet cases of financial restatement continue to occur as a result of misstatements in corporate reporting. This study examines the influence of audit committee size, the frequency of audit committee meetings, and firm size on the probability of financial restatements among subsector companies listed on the Indonesia Stock Exchange during the 2021 to 2023 period. The research applies a quantitative approach using regression analysis to evaluate the relationship between governance mechanisms and restatement occurrence. The results reveal that audit committee size and the frequency of meetings do not have a statistically significant effect on the likelihood of financial restatements. In contrast, firm size shows a significant negative effect, indicating that larger companies tend to experience fewer restatements, possibly due to stronger internal controls, better resources, and more established reporting systems. When analyzed simultaneously, all three variables demonstrate a significant combined effect, highlighting the continued importance of both corporate governance structures and firm characteristics in ensuring high quality financial reporting. These findings suggest that while audit committee attributes alone may not directly prevent restatements, the overall governance environment and organizational scale play a crucial role in maintaining the reliability and credibility of financial statements.